A Model of Lexical Explicitation in Literary Translation - Vahedi Kia, Mehdi (Iranian Journal of Translation Studies, 2011)
The present paper sets out to introduce a model of explicitation in literary translation. The paper opens with a brief review of the notion of explicitation and the way it has been treated in translation taking a lexical approach. Further, our proposed model will be brought forward which will encompass eleven categories of addition to the text where such additions are recoverable from the context and hence believed to pertain to explicitation. The model primarily aims at providing more details than the criteria used for distinguishing explicitation in most research in this area. The examples of explicitation presented for each category are taken from English translations of modern Persian literary texts in the study. The paper may shed light on explicitation as a tendency observed in translations and its different types of occurrence and can be used in translation training courses. Moreover, the model may well serve as a means to enhance self-awareness in translators helping researchers in psycholinguistic-oriented approaches to the study of translation.